2018
DOI: 10.1175/mwr-d-17-0160.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Winter Storm Forecasts with Observing System Simulation Experiments (OSSEs). Part I: An Idealized Case Study of Three U.S. Storms

Abstract: Severe weather events can have a significant impact on local communities because of the loss of life and property. Forecast busts associated with high-impact weather events have been attributed to initial condition errors over data-sparse regions, such as the Pacific Ocean. Numerous flight campaigns have found that targeted observations over these areas can improve forecasts. To better understand the impacts of measurement type and sampling domains on forecast performance, observing system simulation experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 56 publications
4
20
0
Order By: Relevance
“…This OSSE framework consisting of the T511 NR with the global GFS model has been previously developed and validated (Errico et al, ; Privé et al, ) and utilized for several applications including the impacts of rawinsondes (Privé, Errico, & Tai, ). More details on this OSSE framework are also provided in Part 1 of this project (Peevey et al, ).…”
Section: Methods and Designmentioning
confidence: 99%
See 4 more Smart Citations
“…This OSSE framework consisting of the T511 NR with the global GFS model has been previously developed and validated (Errico et al, ; Privé et al, ) and utilized for several applications including the impacts of rawinsondes (Privé, Errico, & Tai, ). More details on this OSSE framework are also provided in Part 1 of this project (Peevey et al, ).…”
Section: Methods and Designmentioning
confidence: 99%
“…The Flight Path domain assumes that the simulated aircraft flies only over ocean and samples for ~ 24 hr, which is comparable to an operational Global Hawk aircraft. More details on the three dropsonde domains are provided in Peevey et al (). All dropsonde experiments assimilate temperature, wind, and humidity, since in Part 1 of this project we found that assimilating all three measurements provides the largest forecast improvement (Peevey et al, ).…”
Section: Methods and Designmentioning
confidence: 99%
See 3 more Smart Citations